Effectiveness of Relaxation Techniques in Reducing Labor Pain: A Systematic Review of Randomized and Observational Studies - Widya Maya Ningrum; Kurniati Devi Purnamasari; Shifa Marlieva (Universitas Galuh, 2025)
Labor pain is a complex experience that may affect maternal outcomes if not properly managed. Relaxation techniques are increasingly used as safe non-pharmacological interventions. To evaluate the effectiveness of relaxation techniques in reducing labor pain. A systematic review following PRISMA 2020 was conducted using PubMed, Scopus, Web of Science, and ScienceDirect (2019–2024). Randomized controlled trials and observational studies assessing relaxation techniques were included. Risk of bias was evaluated using RoB 2 and JBI tools. Thirty-four studies (18 RCTs, 16 observational) were included. Relaxation techniques reduced labor pain by 1.5–3.0 points on the VAS. Hypnobirthing and combined techniques showed the strongest effects, while breathing and mindfulness provided consistent moderate benefits. Relaxation techniques are effective and safe for reducing labor pain and should be integrated into midwifery care.